The Analysis of Bandwidth Management Implementation at Christian University of Indonesia by Using the PS3500 Bluecoat Device - Lumbantoruan, Rutman (Universitas Kristen Indonesia, 2017)
Traffic discovery is an identification process of software and traffic which passes wide area network (WAN) link. In one analyzing process, traffic discovery could identify 10 most active application in bandwidth usage, average bit use per second, and total percentage of bandwidth usage from each application. A study showed traffic network pattern and mirrored bandwidth usage pattern will change in future orderly. Network assessment report encourages traffic pattern. The key is web traffic Hypertext Transfer Protocol (HTTP), If there is an application is considered important traffic, it should become priority. Various non business applications which in network should be limited or time controlled. Recreational traffic such as facebook and youtube will make traffic of critical application slower, it should be limited, controlled, or banned Kata Kunci : Bandwidth, Traffic, Bluecoat